Studi Eksperimen Terhadap Keausan Pada Roda Gigi Cacing Komposit - Rakhmad Arief Siregar; K Umurani; Mukhlas Mukhlas (Fakultas Teknik UMSU, 2019)
The gears are used to transmit power and rotation in various engineering applications. Worm gear is a type of gear that is popularly used to reduce rotation. This study was carried out experimentally to observe the effect of load on rotation on the pair of worm and spur gears made of composite material. A series of loads are applied to the gear pair without lubrication to observe wear on the worm gear. The results show that the greatest wear on the worm gear is located in the middle, namely the threads 4 and 5 of 11.54% and 12.31% respectively with the wear located on the face with a slight bit of flank leading to the pitch diameter.